Order controlled dislocations and grain boundary mobility in Fe–Al–Cr alloys - Lambri, Osvaldo Agustin F. (2012)
The dislocations and grain boundary mobility in elastic range of loading has been analysed by means of mechanical spectroscopy and neutron diffraction studies in Fe–25at.%Al–8at.%Cr and Fe–25at.%Al– 25at.%Cr alloys, in relation to the order degree of the structure. If the alloys are in the ordered state (D03 or B2), the mobility of dislocations and grain boundaries is markedly reduced promoting small values of damping. In contrast, when the ordering is suppressed by annealing at temperatures above 973 K, the mobility of dislocations and grain boundaries increases. This leads to an increase in overall damping. In particular, thermally activated damping peaks related to the solute grain boundary peaks due to presence of the aluminium and chromium atoms appear within the temperature interval from 900 to 1100 K, depending on the substitutional atomic content.